A Tentative Model for the Origin of A-Type Granitoids - Åke Johansson (Minerals, 2023)
A-type granites are typically formed in stable intra-plate, back-arc or postcollisional settings and are characterized by highly ferroan and potassic major element compositions, and by strong enrichment in incompatible trace elements. Unlike I-, S- and M-type granites, where the letters denote the dominant source material (igneous, sedimentary or mantle derived), there is no consensus on the source and processes giving rise to A-type magmas. In this contribution, a conceptual model for the origin of A-type granitoids, using the Bornholm A-type granitoid complex in southern Fennoscandia as an example, is presented. In this model, underplated mantle-derived basaltic magma may develop into intermediate and siliceous A-type magma, which is ferroan, potassic and highly enriched in incompatible trace elements, through a combination of fractional crystallization leading to cumulate formation, and partial melting and crustal assimilation, in a process akin to zone refining in metallurgy. The key factor is a relatively stable tectonic environment (postcollisional, anorogenic, or extensional), where there is little or no replenishment of more primitive basaltic magma to the system, allowing it to attain more evolved, enriched and extreme compositions. The A-type granitoids may then be viewed as a more evolved counterpart of subduction-related I-type granitoids.